2015
DOI: 10.1007/s00253-015-6833-5
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling glutathione conjugate catabolism in Saccharomyces cerevisiae: the role of glutathione/dipeptide transporters and vacuolar function in the release of volatile sulfur compounds 3-mercaptohexan-1-ol and 4-mercapto-4-methylpentan-2-one

Abstract: Sulfur-containing aroma compounds are key contributors to the flavour of a diverse range of foods and beverages, such as wine. The tropical fruit characters of Sauvignon Blanc wines are attributed to the presence of the aromatic thiols 3-mercaptohexan-1-ol (3-MH), its acetate ester 3-mercaptohexyl acetate (3-MHA), and 4-mercapto-4-methylpentan-2-one (4-MMP). These aromatic thiols are not detectable in grape juice to any significant extent but are released by yeast during alcoholic fermentation. While the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 78 publications
(116 reference statements)
1
44
0
Order By: Relevance
“…Furthermore, based on conversion yields, it appeared that Cys-3SH was more easily utilised by yeast in the release of 3SH [23] -a substantially lower conversion efficiency for GSH-3SH has since been shown [24] due to the need for yeast to first convert the GSH precursor to its Cys counterpart. [25] …”
Section: Conversion Of 3sh Precursors During Fermentationstereochemicmentioning
confidence: 99%
“…Furthermore, based on conversion yields, it appeared that Cys-3SH was more easily utilised by yeast in the release of 3SH [23] -a substantially lower conversion efficiency for GSH-3SH has since been shown [24] due to the need for yeast to first convert the GSH precursor to its Cys counterpart. [25] …”
Section: Conversion Of 3sh Precursors During Fermentationstereochemicmentioning
confidence: 99%
“…It has been shown that 4-MMP and 3-MH exist in the grape berry as nonvolatile precursors, mainly as conjugates of glutathione (Glut-4-MMP and Glut-3-MH) and cysteine (Cys-4-MMP and Cys-3-MH) (18,19). Dipeptide conjugates of 3-MH, S-3cysteinyl glycinylhexan-1-ol (Cys-Gly-3-MH), and S-3-␥-glutamyl cysteinylhexan-1-ol (␥-Glu-Cys-3-MH) have also been identified (20)(21)(22). The acetate ester of 3-MH (3-MHA) is not formed from a nonvolatile precursor but results from acetylation of 3-MH by the yeast alcohol acetyltransferase ATF1 (23).…”
mentioning
confidence: 99%
“…The acetate ester of 3-MH (3-MHA) is not formed from a nonvolatile precursor but results from acetylation of 3-MH by the yeast alcohol acetyltransferase ATF1 (23). Biotransformation of conjugated precursors into free thiols by yeast involves their uptake through amino acid and glutathione (GSH) transporters in the plasma membrane (21,24,25). Once inside the cytoplasm, Glut-3-MH is cleaved to Cys-Gly-3-MH in the yeast vacuole by action of the ␥-glutamate transpeptidase ECM38, which might also catalyze the formation of Cys-3-MH from the precursor dipeptide ␥-Glu-Cys-3-MH (21,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In all winery yeast strains GEX1 was detectable, which is suggested to increase the glutathione concentration in wine . However, the exact mechanism of glutathione export and the relative importance of GEX1 is still unclear . In the case of S288c, it was possible to verify our PCR screening to the specific DMGs, because of the findings of Nakao et al .…”
Section: Discussionmentioning
confidence: 97%